2011
DOI: 10.1161/atvbaha.111.229443
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Eicosapentaenoic Acid Induces Rapid Regression of Atherosclerosis Via Modulating the Phenotype of Dendritic Cells in LDL Receptor-Deficient Mice

Abstract: In addition to lowering plasma cholesterol, EPA regressed atherosclerosis probably due to modulation of DC phenotype and reduction in T cell numbers. The present findings might partly explain the beneficial effects of EPA in clinics and support clinical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 28 publications
2
64
2
Order By: Relevance
“…Growing evidences are being accumulated regarding the fact that ω3-PUFA administration can decrease the expression of MCP-1 and endothelial adhesion molecules, such as intercellular adhesion molecule-1, VCAM-1 and selectin, resulting in the inhibition of macrophage invasion into the vascular endothelium. 24, 25 Thus, the endothelium macrophage interaction and the inflammatory mediators secreted by infiltrating cells triggered by AngII infusion may be suppressed by administration of ω3-PUFAs, which is more likely to enhance the mechanism underlying the suppression of vascular inflammation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences are being accumulated regarding the fact that ω3-PUFA administration can decrease the expression of MCP-1 and endothelial adhesion molecules, such as intercellular adhesion molecule-1, VCAM-1 and selectin, resulting in the inhibition of macrophage invasion into the vascular endothelium. 24, 25 Thus, the endothelium macrophage interaction and the inflammatory mediators secreted by infiltrating cells triggered by AngII infusion may be suppressed by administration of ω3-PUFAs, which is more likely to enhance the mechanism underlying the suppression of vascular inflammation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although not yet successful, therapeutic interventions targeting the atherosclerotic inflammatory process described may lead to establishment of definitive treatments for atherosclerotic CVD. [9][10][11][12][13][14] Intestine as a Therapeutic Target for Preventing Atherosclerosis…”
Section: Proinflammatory and Antiinflammatory Immune Responses In Athmentioning
confidence: 99%
“…Although actual subtypes of DCs in the small intestine and atherosclerotic lesions in our experiment remain unclear, calcitriol enhances the proportion of immature DCs and modulates the function of DCs, which exist in the small intestine and within atherosclerotic plaques. Importantly, we have already reported that tolerogenic DCs overexpressing IDO play a critical role in atherosclerotic regression in a mouse model 53) . Oral administration of eicosapentaenoic acid reduces the expression of co-stimulatory molecules on DCs and induces IDO expression in DCs existed within lymph nodes in the intestine and spleen.…”
Section: Cd11bmentioning
confidence: 95%